Au/Pt co-loaded ultrathin TiO2 nanosheets for photocatalyzed H2 evolution by the synergistic effect of plasmonic enhancement and co-catalysis. Issue 119 (18th November 2015) - Chen, Changyu; Kuai, Long; Chen, Yanjun; Wang, Qing; Kan, Erjie; Geng, Baoyou
Abstract : The synergistic functions of plasmonic enhancement and co-catalysis by photo-depositing Au and Pt nanoparticles on a TiO2 surface were investigated, in which Au stimulates the plasmonic effect and Pt acts as the co-catalyst. Abstract : Co-catalysis and plasmonic enhancement are two efficient ways to improve the photocatalytic performance of semiconductors. In this work, we systematically investigate their synergistic functions by photo-depositing Au and Pt nanoparticles on the surface of ultrathin TiO2 nanosheets, where Au stimulates the plasmonic effect and Pt acts as the co-catalyst. It was found that both Au and Pt deposition can increase the H2 production rate. More importantly, faster H2 production can be obtained with the co-loading of Au and Pt. Furthermore, a suitable Au loading was important for the photocatalytic performance. As a consequence, the highest H2 rate of 7.19 mmol g −1 h −1 was achieved by depositing 0.75% Pt and 0.5% Au on TiO2 . Therefore, this work presents the synergistic effect between the plasmonic enhancement of Au and the co-catalysis of Pt for photocatalytic H2 production, which contributes some guidance to catalyst design and preparation.